Endogenous governance transparency and product market competition - Ana Hidalgo-Cabrillana (SERIEs - Journal of the Spanish Economic Association, 2013)
This paper analyzes the determinants of governance transparency. In our model, entrepreneurs optimally decide the precision of their earning reporting by trading off the possibility of expropriating profits against the capacity to attract external funding.We find that information is only valuable if enough quality of it is disclosed. Otherwise, the entrepreneur will always pretend to be unsuccessful and the capital market will break down. If, by contrast, a minimum precision level is ensured, fund diversion will be zero but full disclosure is still not achieved.We showthat an important driving force behind governance transparency is product market competition. Tougher competition leads to more firms competing for funding, which in turn changes how resources are allocated since each individual firm becomes less important in the portfolio choice. Firms react to this loss of market power by increasing transparency. Furthermore, firms characterized by low corporate profits or firms in a country with a strong legal system will be more likely to avoid voluntary disclosure regimes.
Keywords: D82; G11; G32; G34; 330; corporate governance; voluntary disclosure; portfolio choice; incentives; product market competition